Large eddy simulation of soot formation in a ducted fuel injection configuration. (1st April 2022) - Ong, Jiun Cai; Zhang, Min; Jensen, Morten Skov; Walther, Jens Honoré
Abstract: The aim of this numerical study is to investigate the soot formation processes in a ducted fuel injection (DFI) spray under engine-like conditions. Furthermore, the effect of the pre-injection dwell period on the spray, combustion, and soot characteristics are also investigated. The DFI configuration considered here is D3L14G2. Large eddy simulations coupled with a two-equation soot model and conjugated heat transfer are performed. Inert and reacting spray simulations conducted for the free spray (FS) and DFI-configurations are validated against measured data. Reasonable agreement to the measurements is achieved for the simulated ignition delay time (IDT) and lift-off length (LOL) under FS configuration. The dwelling period is shown to significantly affect the combustion characteristics in the DFI-configuration. A dwell time of 1 seconds causes longer IDT and LOL, which leads to them being closer to the measured data. In contrast, the IDT and LOL predicted in the non-dwelled DFI case are significantly shorter and the ignition sites are shown to form inside the duct. The difference between dwelled and non-dwelled case is due to the presence of thermal boundary layer in the former case. In the dwelled DFI case, the increase in LOL leads to a higher overall air entrainment process and better air–fuel mixing. This in turn decreases the soot precursor C2 H2 -mass spike by two-fold and the soot mass spike by three-fold relative to that obtained in the FS case. Hence, the present study highlights the significance of the dwell period for this particular DFI configuration (D3L14G2). Omitting this crucial step in a DFI setup is demonstrated in this study to cause ignition to occur inside the duct, which consequently lead to a greater soot mass spike than that in the FS case. Highlights: Soot reduction effect in duct fuel injection configuration is captured using LES. Dwelling time causes thermal boundary layer to form inside the duct before injection. Thermal boundary layer in duct causes ignition further downstream and longer LOL. In DFI, longer LOL leads to better air entrainment process, hence less soot formed.